Insurance type and risk of dementia diagnosis after traumatic brain injury: a study of 267 473 US civilians from 2000 to 2022 - Paola Gilsanz; Rachel A Whitmer; Miriam Nuño; Maxwell Boakye; Beatrice Ugiliweneza; Maya Deshmukh (BMJ Open, 2025)
Objectives To evaluate how insurance influences the risk of a dementia diagnosis among a large, diverse cohort of US civilian adults with traumatic brain injury (TBI) over a 22-year period.Design This is a retrospective cohort study involving individuals diagnosed with TBI.Setting The study used the Merative MarketScan Research Database, specifically drawing from the Commercial Claims and Encounters, Medicare Supplemental and Medicaid databases, from 2000 to 2022 in the USA. These databases provide comprehensive insights into healthcare services received by enrollees, including inpatient and outpatient services, outpatient prescription claims, clinical utilisation records and healthcare expenditures.Participants 267 473 adults aged 55 and older who were diagnosed with a TBI between 1 January 2000 and 31 December 2022. Individuals with unknown TBI severity and dementia claims 2 years preceding TBI were excluded. TBI and dementia diagnoses were identified using International Classification of Disease 9th and 10th editions codes from inpatient and outpatient admission records.Interventions None.Primary and secondary outcome measures We compared the incidence of all-cause dementia across different insurance types to assess potential disparities in diagnosis following TBI. Cox proportional hazards models, with age as the time scale, were used to study the association between insurance type and dementia diagnosis following a TBI. Models were adjusted for key demographic variables, medical comorbidities and psychiatric conditions to account for potential confounding.Results Of the 267 473 individuals with TBI, 12.7% were diagnosed with dementia over a mean follow-up period of 40 months (SD of 42 months). Dementia incidence differed significantly by insurance type, with 18.2% for Medicaid recipients, 17.3% for Medicare beneficiaries and only 2.3% among individuals with commercial insurance. The adjusted HR for dementia was notably higher among individuals enrolled on Medicaid (HR 2.9, 95% CI: 2.8 to 3.1) and Medicare (HR 2.1, 95% CI: 2.0 to 2.2), when compared with those with commercial insurance.Conclusions Individuals with TBI covered by Medicaid and Medicare are significantly more likely to be diagnosed with dementia, with a 2.9-fold and 2.1-fold increase risk, respectively, compared with those with commercial insurance. Addressing insurance-related disparities in dementia diagnosis is crucial for building a more equitable healthcare system. It is essential that individuals with TBI cases, regardless of their insurance type, have access to comprehensive care and preventive interventions to achieve the best possible long-term outcomes.